2009
DOI: 10.1111/j.1600-0587.2009.05612.x
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of fishes and invertebrates to prolonged drought in two California streams

Abstract: Long-term data are needed to assess spatial and temporal variability of communities and their resilience to natural and anthropogenic disturbances, particularly in climatic regions marked by high interannual variability (e.g. mediterraneanclimate). A long-term study at four sites on two streams in mediterranean-climate California (annual sampling over 20 yr) allowed us to quantify the influence of a 5-yr prolonged drought on stream invertebrate and fish communities. Invertebrate community composition did not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
122
4
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 42 publications
2
122
4
2
Order By: Relevance
“…Comparisons between wet and dry years have shown that richness and exclusive species are higher in wet than in dry years, which has been related to relatively higher habitat availability in wetter years [83]. However, other studies did not observe these differences in macroinvertebrate richness [21]. For macroinvertebrate density, no significant differences between wet and dry years are reported [21,84].…”
Section: Macroinvertebrate Communitiesmentioning
confidence: 58%
See 2 more Smart Citations
“…Comparisons between wet and dry years have shown that richness and exclusive species are higher in wet than in dry years, which has been related to relatively higher habitat availability in wetter years [83]. However, other studies did not observe these differences in macroinvertebrate richness [21]. For macroinvertebrate density, no significant differences between wet and dry years are reported [21,84].…”
Section: Macroinvertebrate Communitiesmentioning
confidence: 58%
“…However, other studies did not observe these differences in macroinvertebrate richness [21]. For macroinvertebrate density, no significant differences between wet and dry years are reported [21,84].…”
Section: Macroinvertebrate Communitiesmentioning
confidence: 75%
See 1 more Smart Citation
“…Our work suggested that, to adequately represent patterns in densities, models will need to incorporate both local-scale and landscapescale variables that include interactions and nonlinear relationships. Further studies are in progress, but it seems likely that best approaches will require relatively long-term data and sophisticated modelling tools such as mixed-effects models (Beˆche et al 2009), regression trees (Elith et al 2008) or artificial neural networks (Joy & Death 2004). Consideration of diel variations in local-scale habitat preferences, as has been investigated for other New Zealand native fishes (Davey et al 2010), may also be an area which would benefit from further research.…”
Section: Future Directionsmentioning
confidence: 99%
“…The seasonal drying and rewetting pattern produces a wide array of temporarily inundated aquatic habitats, including seasonal floodplains, wetlands, off-channel ponds, and streams (Gasith and Resh 1999;Bonada et al 2008; *Corresponding author. Email: bec.lorig@gmail.com Beˆche et al 2009). The seasonal aquatic habitats generally retain their connection to permanent water sources for a period of three to seven months due to the predictable precipitation patterns.…”
mentioning
confidence: 99%